Cohen's kappa curves, new geometrical forms of dual curves - Laith H. M. Al-ossmi; Imad Ibrahim Dawood (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
In this article, we introduce the concepts of taxicab and uniform products in the context of dual curves associated with Cohen's kappa, primarily defined by a set of inflection curvatures of an ellipse and a circle using parallel asymptotes. The novel curve under scrutiny, denominated as the